Discourse conditions on subject pronoun realization: Testing the linguistic intuitions of older bilingual children - Sorace, Antonella; Serratrice, Ludovica; Filiaci, Francesca; Baldo, Michela (Lingua, 2009)
This study investigates the acceptability of Italian and English pronominal subject forms in −topic shift [−TS] and +topic shift [+TS] contexts in English-Italian and Spanish-Italian bilingual children aged 6–7 and 8–10, age-matched monolingual children, and monolingual adults. The aim was to disentangle possible effects of cross-linguistic influence from the more general effects of bilingualism and the use of ‘default’ forms. A further aim of the study was to test the influence of input and exposure to Italian by comparing bilinguals living in Italy and bilinguals living in the UK. The results showed no statistically significant differences in English: regardless of age, language combination, and language of the community, participants overwhelmingly rejected ungrammatical sentences with a missing subject and chose sentences with an overt subject pronoun. In Italian, by contrast, the patterns of results were much more varied. Younger monolingual and bilingual children chose significantly more pragmatically inappropriate overt subject pronouns than older children and adults. A significant interaction between age and language of the community also showed that at the age of 6–7 English-Italian bilinguals in the UK chose significantly more pragmatically overt pronouns than all the other groups of children, while at the age of 8–10 it was the Spanish-Italian bilinguals that performed significantly less accurately than all other groups of children. Bilingual children, regardless of age and language combination, also accepted some infelicitous null subject pronouns. This pattern of results indicates that variables beside cross-linguistic influence must be considered as explanatory factors in this particular domain. It also suggests that it is important to differentiate among different discourse conditions affecting subject pronouns in context.